2000
DOI: 10.1590/s0301-80592000000100004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da toxicidade aguda (DL50 e CL50) de inseticidas para Scaptotrigona tubiba (Smith) (Hymenoptera: Apidae): via de contato

Abstract: Visando avaliar a toxicidade aguda de alguns inseticidas para Scaptotrigona tubiba (Smith) e discutir a aplicabilidade de testes de contato por aplicação tópica e filme seco, foram realizados testes com operárias capturadas na entrada da colméia e divididas em grupos de quatro repetições de cinco abelhas cada, sendo mantidas em placas de Petri forradas com papel de filtro por 48 h, com alimentação constante. Os produtos testados foram: deltametrina, Bacillus thuringiensis, triclorfom e malatiom diluídos em águ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
1
13
1
7
Order By: Relevance
“…The calculated LD 50 for the Western honey bee to permethrin, diazinon, and methomyl were 0.159, 0.372, and 1.29 g per bee, respectively (Atkins et al 1981), which are signiÞ-cantly higher than the lethal doses that we found for the same chemicals on the three studied stingless bees. Our results and the Þndings by Moraes et al (2000) in Scaptotrigona tubiba (Smith) indicate that stingless bees are highly susceptible to some pesticides. Nevertheless, it is reported that species such as Scapto- The values of the chi-square test for each slope (b) are presented as well as the PearsonÕs correlations between wt and LD 50 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The calculated LD 50 for the Western honey bee to permethrin, diazinon, and methomyl were 0.159, 0.372, and 1.29 g per bee, respectively (Atkins et al 1981), which are signiÞ-cantly higher than the lethal doses that we found for the same chemicals on the three studied stingless bees. Our results and the Þndings by Moraes et al (2000) in Scaptotrigona tubiba (Smith) indicate that stingless bees are highly susceptible to some pesticides. Nevertheless, it is reported that species such as Scapto- The values of the chi-square test for each slope (b) are presented as well as the PearsonÕs correlations between wt and LD 50 .…”
Section: Discussionsupporting
confidence: 61%
“…Pioneering studies in Brazil have evidenced the toxicity of insecticides to workers of stingless bees (Malaspina and Stort 1983, Macieira and Hebling-Beraldo 1989, Moraes et al 2000. However, comparison between species has not been conducted and the role of factors such as age and size in relation to the relative resistance remains unclear.…”
mentioning
confidence: 99%
“…Most studies on the effects of pesticides on bees have evaluated the adult stage (Moraes et al 2000), mainly using the species Apis mellifera as a study model (Cresswell 2011;Costa et al 2014;Fairbrother et al 2014). Studies on the exposure of bees during the larval stage through in vitro rearing tests also focus on this species (Aupinel et al 2007;Hendriksma et al 2011;Wilkins et al 2013;Tavares et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos comparativos sobre a suscetibilidade de espécies da fauna brasileira evidenciaram a alta toxicidade de diferentes ingredientes ativos para esse grupo de espécies: permetrina, heptacloro, dieldrina, cipermetrina, endossulfam, malationa, acetato, carbaril e fenvalerato para Trigona spinipes (Macieira & Hebling-Beraldo, 1989); deltametrina, triclorfom e malationa para Scaptotrigona tubiba (Moraes et al, 2000); deltametrina e metamidofós para Melipona quadrifasciata (Del Sarto et al, 2014), imidacloprido para Melipona scutellaris (Costa et al, 2015) e Scaptotrigona postica ; fipronil para M. scutellaris (Lourenço et al, 2012a(Lourenço et al, , 2012b e S. postica (Jacob et al, 2013). Muitos desses ingredientes ativos, durante sua rota metabólica, afetam diferentes processos celulares que impactam a longevidade, o comportamento e a fisiologia do inseto, e podem causar efeitos individuais e consequências para a colônia ao longo do tempo.…”
Section: O Uso De Agrotóxicos Na Agriculturaunclassified